PROTECT PEOPLE FROM EXPOSURE TO SECONDHAND SMOKE IN FEDERALLY-FUNDED CHILDREN'S PROGRAMS AND FEDERAL BUILDINGS (Tufts Archival Research Center, 2007)
Letter from Richard Durbin and other Representatives hoping to gain support for legislation protecting children from secondhand smoke exposure in federally funded programs.